ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN PRODUK SUSU MURNI KPUB SAPI JAYA MENGGUNAKAN METODE REGRESI LINEAR BERGANDA: ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN PRODUK SUSU MURNI KPUB SAPI JAYA MENGGUNAKAN METODE REGRESI LINEAR BERGANDA - Aziz Muslih; Sumarsono; Andhika Mayasari (INVANTRI (Inovasi Dan Pengelolaan Industri), 2023)
Customer satisfaction became one major priority for business agent to attract customer buying interest. Customer satisfaction is the feeling of happiness or sadness which appear after buying and comparing the product with other brands. The process of getting good Multiple Linear Regression analysis result in this research, then it has to be examined in these following steps: (1) Testing the validity and reliability of questionnaire measuring instruments. (2) Describing variables of the research. (3) Testing the classical assumptions such as heterokedasticity, multicollinearity, collinearity and normality test. (4) Analyzing Multiple Linear Regression, which includes the F_test (joint test), t_test (partial test), and the coefiicient of detemination (R-squared) test. Identification values of the factors that affect customer satisfaction towards KPUB Sapi Jaya pure milk products obtained from the result of the linear regression equation, where the value of the influence constituent is 2,117 units, the value of the influence of X1. of 0.367 units, the value of influence X3. Product features of 0.671 units, the value of influence X4. The product beauty is 0.259, the value of influence X5. The perceived quality is 0.814 units and the value of influence X6. Service is 0.211 units. Furthermore, the results of the significance test, which significantly affects customer satisfaction of KPUB Sapi Jaya pure milk products, it is concluded that there are 2 factors, the first is product durability factor (X1) and the second is perceived quality factor (X5). Meanwhile 4 other factors are not significant, such as product suitability factor (X2); product features (X3); beauty products (X4) and services (X6).